Direct Synthesis of a Covalently Self‐Assembled Peptide Nanogel from a Tyrosine‐Rich Peptide Monomer and Its Biomineralized Hybrids. (23rd April 2018) - Min, Kyoung‐Ik; Kim, Dong‐Hwi; Lee, Hyune‐Jea; Lin, Liwei; Kim, Dong‐Pyo
Abstract: There has been significant progress in the self‐assembly of biological materials, but the one‐step covalent peptide self‐assembly for well‐defined nanostructures is still in its infancy. Inspired by the biological functions of tyrosine, a covalently assembled fluorescent peptide nanogel is developed by a ruthenium‐mediated, one‐step photo‐crosslinking of tyrosine‐rich short peptides under the visible light within 6 minutes. The covalently assembled peptide nanogel is stable in various organic solvents and different pH levels, unlike those made from vulnerable non‐covalent assemblies. The semipermeable peptide nanogel with a high density of redox‐active tyrosine acts as a novel nano‐bioreactor, allowing the formation of uniform metal–peptide hybrids by selective biomineralization under UV irradiation. As such, this peptide nanogel could be useful in the design of novel nanohybrids and peptidosomes possessing functional nanomaterials.